Pandangan Masyarakat Terhadap Kehidupan Perempuan Malam pada Musik Karaoke 999 di KelurahaN TIPULU KECAMATAN KENDARI BARAT KOTA KENDARI - Nur Khoiriah, Wa Ode; Sukur, La Ode (JURNAL KABANTI: Kerabat Antropologi, 2025)
This study aims to understand public perceptions of the presence of women working as song guides (Lady Companions) at Karaoke 999 and to explore the reasons why these women choose to work in such establishments. Using Henrietta Moore’s theory of Gender and Power, the research adopts a qualitative approach through direct observation and interviews. The findings reveal that the community in Tipulu Sub-district generally holds negative views toward women working in nightlife karaoke, associating them with alcohol consumption and entertainment roles. The main reasons women choose to work as Lady Companions include economic factors, low educational background, environmental influences, and the impact of divorce.